Levels of zinc sulfate in field corn ( Zea mays ) grown in campo-cerrados - Pereira, João; Vieira, Iron F.; Moraes, Ednan Araújo; Rêgo, Abelardo S. (Pesquisa Agropecuaria Brasileira, 2014)
The Anápolis Experimental Station (Brazil), executed a field experiment, in replicated plots, using a basic NPK-Ca fertilization and 6 levels of zine sulphate, applied to the soil: 0, 10, 20, 30, 40 and 50 kg/ha. This was done on a Red-dark Latosol, campo-cerrado phase, during two consecutive years. Zinc application showed a significant fourth degree response both year, but there was no significante among the zinc levels, except for O and 10 levels, lo the present case, to can he concluded that zinc gave a high response in production, when applied in campo-cerrado. There was no phytotoxic effect due to the high zinc levels.